Mother Teresa - "Watts, Greg" (Noida, 2009)
In your own way, try to make the world conscious that it is never too late to do something beautiful for God.' - Mother Teresa, in a letter to Malcolm Muggeridge In 1969, Malcolm Muggeridge travelled to Calcutta to make a documentary about Mother Teresa with the BBC. Muggeridge was immediately impressed on his first meeting with her and his resulting documentary, Something Beautiful for God, brought Mother Teresa to the attention of the world's media and public. Following the documentary trip, Muggeridge wrote this book (originally published in 1971), which combines his reflections about Mother Teresa, her work and the time he spent with her, quotes from Mother Teresa on a wide range of topics and an in-depth interview between Mother Teresa and Muggeridge. This labour of love is as much the author's personal homage as it is an uplifting chronicle of his discovery of Mother Teresa and the religious order she instituted.
Keywords: Mother Teresa-Biography